Interference with CHD1L inhibits the malignant progression and enhances cisplatin sensitivity of ovarian cancer cells by binding PLK1 - Kun Qiao; Yuanxiazi Guan; Wenjing Xing (Journal of Ovarian Research)
Abstract Background Chromodomain helicase/ATPase DNA-binding protein 1-like gene (CHDIL) is an oncogene with abnormal expression in ovarian cancer (OC), but its regulatory role in the malignant biological properties of OC cells and its mechanisms have not been reported. Methods In this study, CHD1L and polo-like Kinase 1 (PLK1) expression in OC tissues and OC cell lines was analyzed. After CHD1L silencing, CAOV-3 cell proliferation and apoptosis were detected by CCK8 assay, EDU and TUNEL staining. Flow cytometry was used to detect cell cycle. CCK8 assay and TUNEL were used to detect the role of CHD1L in the sensitivity of OC cells to cisplatin. In addition, the abilities of CAOV-3 cell migration and invasion were evaluated using wound healing assay and transwell assay. Next, the binding between CHD1L and PLK1 was investigated using co-immunoprecipitation assay. Then, PLK1 was overexpressed to perform the rescue experiments to analyze the regulation mechanism of CHD1L on OC development and cisplatin sensitivity. Moreover, the transplantation tumor model of CAOV-3 cells in nude mice was established to explore the antineoplastic effect of CHD1L downregulation in vivo. Results CHD1L was highly expressed in OC tissues and OC cells. Interference with CHD1L significantly inhibited proliferation, promoted apoptosis, induced cycle arrest, suppressed migration and invasion as well as enhanced the sensitivity of CAOV-3 cells to cisplatin. Additionally, CHD1L could interact with PLK1. PLK1 upregulation restored the impacts of CHD1L knockdown on the proliferation, apoptosis, cycle arrest, migration, invasion and the sensitivity of OC cells to cisplatin. It could be also found that CHD1L knocked down limited the tumor volume, downregulated PLK1, Ki67 and cleaved caspse3 expression. Conclusion Taken together, interference with CHD1L inhibited the malignant progression and enhanced cisplatin sensitivity of OC cells by binding PLK1.